2016
DOI: 10.5465/amr.2014.0208
|View full text |Cite
|
Sign up to set email alerts
|

On the Forgetting of Corporate Irresponsibility

Abstract: Why are some serious cases of corporate irresponsibility collectively forgotten? Drawing on social memory studies, we examine how this collective forgetting process can occur. We propose that a major instance of corporate irresponsibility leads to the emergence of a stakeholder mnemonic community that shares a common recollection of the past incident. This community generates and then draws on mnemonic traces to sustain a collective memory of the past event over time. In addition to the natural entropic tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
195
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(206 citation statements)
references
References 136 publications
(218 reference statements)
2
195
2
7
Order By: Relevance
“…James et al, 2011). Here our findings also run counter to prior studies suggesting that firms are able to erase memories of their transgressions in the mid to long term (Mena et al, 2016). Instead, we found that a transgression can pass into collective memory and make a community permanently hostile towards the marketer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…James et al, 2011). Here our findings also run counter to prior studies suggesting that firms are able to erase memories of their transgressions in the mid to long term (Mena et al, 2016). Instead, we found that a transgression can pass into collective memory and make a community permanently hostile towards the marketer.…”
Section: Discussioncontrasting
confidence: 99%
“…I STILL don't trust Bioware after the ending to [ME3] and the babyrage that followed from their staff members. (Adam, KitGuru Blog, February 2016) Whereas organizational transgressions often rouse initial attention but are eventually forgotten (Mena et al, 2016), the memory of Bioware's perceived transgression has remained alive for years. At the extreme, community members hijack official marketer commemorations.…”
Section: Remembrance: Passing the Transgression Into Collective Memorymentioning
confidence: 99%
“…For example, if a highly profitable and highly polluting company becomes the target of environmental activists, consumer confidence in the company will sink. If this company ultimately files for bankruptcy, investors may infer from this anomaly either that there is a positive CSP-CFP link or, perhaps, that NGOs have become so powerful that companies should become more proficient in covering up the pollution they create (Mena, Rintamäki, Fleming, & Spicer, 2016). We argue that, in this context, sensegiving activities are likely to convince at least some investors that there is a positive link between CSP and CFP.…”
Section: /53mentioning
confidence: 88%
“…Our interest is to include a generic understanding of business responsibilities to society that encompasses business activities that respond to social expectations and have an effect on the public good in the social, political, environmental, and economic environment of the firm. In applying such a broad perspective, we explicitly also include impacts of a detrimental or harmful nature on those environments-which rarely and only recently have entered the debate in mainstream CSR (e.g., Mena et al 2016).…”
Section: Csr and The Public Good In A Business Group Contextmentioning
confidence: 99%